2015
DOI: 10.1186/s12874-015-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing opt-in and opt-out home visits for tracing lost participants in a prospective birth cohort study

Abstract: BackgroundAttrition is an important problem in cohort studies. Tracing cohort members who have moved or otherwise lost contact with the study is vital. There is some debate about the acceptability and relative effectiveness of opt-in versus opt-out methods of contacting cohort members to re-engage them in this context. We conducted a randomised controlled trial to compare the two approaches in terms of effectiveness (tracing to confirm address and consenting to continue in the study), cost-effectiveness and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Compliance issues are an important consideration. Loss to follow-up among postnatal women can range from 30 to 40% [43, 44]. Experience of research in similar populations has shown that planned initiatives including flexible follow-up appointments, travel expenses, vouchers for returning questionnaires, and sending of reminders can reduce loss to follow-up.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Compliance issues are an important consideration. Loss to follow-up among postnatal women can range from 30 to 40% [43, 44]. Experience of research in similar populations has shown that planned initiatives including flexible follow-up appointments, travel expenses, vouchers for returning questionnaires, and sending of reminders can reduce loss to follow-up.…”
Section: Methods and Analysismentioning
confidence: 99%
“…For instance, qualitative research with cohort members has also been conducted in order to explore their views on data linkage [30]. Furthermore, ALSPAC have conducted randomised trials with participants in order to elicit their opinions on materials to improve consent response rates [41], and to explore the effectiveness of opt in versus opt out methods of contacting participants for re-engagement [42]. Finally, participant representation on study committees helps ensure the interests of the cohort members are formally represented on an ongoing basis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Parents and guardians decided whether to opt out from the study by communicating this to settings, preserving their anonymity. This opt-out model of participation was selected because it is more likely to represent families and children from socioeconomically disadvantaged backgrounds in longitudinal designs (Bray et al, 2015).Participants.…”
mentioning
confidence: 99%